2018
DOI: 10.1039/c8ra01944d
|View full text |Cite
|
Sign up to set email alerts
|

Branched copolymer-stabilised nanoemulsions as new candidate oral drug delivery systems

Abstract: Branched copolymers offer very efficient nanoemulsion stabilisers with benefits for oral drug delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Using an epithelium monolayer transwell membrane the permeation of emulsion formulated HIV protease inhibitor Lopinavir was around 10 times higher than the aqueous application of the drug. 163 In a viral activity assay the antiviral effect (against HIV-1 IIIB) of drug-loaded nanoemulsions was similar to the aqueous based control. Additionally, it has been demonstrated that these highly branched polymers, synthesised by ATRP, can form stable nanoparticle composites with super-paramagnetic iron oxide nanoparticles (SPIONs) with future uses for delivery of drugs, imaging agents, or hyperthermia agents within cancer therapies.…”
Section: Divinyl Monomer Copolymerisationmentioning
confidence: 83%
“…Using an epithelium monolayer transwell membrane the permeation of emulsion formulated HIV protease inhibitor Lopinavir was around 10 times higher than the aqueous application of the drug. 163 In a viral activity assay the antiviral effect (against HIV-1 IIIB) of drug-loaded nanoemulsions was similar to the aqueous based control. Additionally, it has been demonstrated that these highly branched polymers, synthesised by ATRP, can form stable nanoparticle composites with super-paramagnetic iron oxide nanoparticles (SPIONs) with future uses for delivery of drugs, imaging agents, or hyperthermia agents within cancer therapies.…”
Section: Divinyl Monomer Copolymerisationmentioning
confidence: 83%
“…Various methods like low-energy emulsification method, phase inversion temperature method ultrasonication, high pressure homogenization, or microfluidization are used for their preparation [ 57 ]. Various oils like soyabean oil, castor oil, and peanut oil have been used as lipids [ 58 ]. NEs have advantages of increasing aqueous solubility, loading capacity, increased residence time in GIT, enhanced absorption and bioavailability, and lymphatic uptake [ 59 ].…”
Section: Nanotechnology Formulation Aspects and Their Application In mentioning
confidence: 99%
“…To the NEs, the lopinavir (Lpv) that inhibits the protease-mediated maturation of virions or efavirenz (Efz) that inhibits the viral RNA reverse transcription was loaded, and both the antiretroviral drug-loaded NEs exhibited enhanced permeability and antiviral activity against HIV-1 IIIB-infected MT4 cells. The apparent permeability of Lpv was almost an order of higher magnitude after 2 hours compared to the control aqueous-DMSO drug solution [ 76 ]. The self-nano emulsifying oil formulations (SNOFs) of Efz prepared with caproyl 90 and kolliphor EL showed a low percent dissolution efficiency and a high dissolution half-life less than 9 min for Efz under in vitro condition compared to free Efz [ 77 ].…”
Section: Essential Oil-based Nes/mes Antiviral and Drug Delivery Systmentioning
confidence: 99%